Pelatihan ToT Strategi Coping Stres dan Pencegahan serta Penanganan Kekerasan Seksual pada Guru untuk Mengatasi Stres dan Mencegah Kekerasan Seksual pada Siswa di SLB Negeri Lobalain di Kabupaten Rote-Ndao [ToT Training on Stress Coping Strategies and the Prevention and Handling of Sexual Violence for Teachers to Address Stress and Prevent Sexual Violence among Students at SLB Negeri Lobalain, Rote-Ndao Regency] - Damayanti, Yeni; Lerik, Mariana Dinah Ch.; Ratu, Feronika; Panis, Marleny Purnamasary (UKInstitute, 2025)
Abstrac. Children and adolescents with disabilities in SLB need to have knowledge about coping stress strategies and understand about sexual violence and its prevention. Training of trainers (ToT) training for teachers in SLB on coping stress and prevention and handling of sexual violence was done for the purpose to provide knowledge for students in SLB on how to overcome stress and prevent sexual violence that are susceptible to be experienced by children and adolescents with disabilities. This training activity is a form of community service carried out on teachers at SLB Negeri Lobalain, Rote-Ndao Regency. A total of 17 teachers participated in this community service activity. A quasi-experimental study with one-group pretest-posttest design was conducted to measure the effectiveness of the training. The results of the hypothesis testing showed that the training has a significant effect on participants' understanding, t(16) = -5.738, p 0.001, d = -1.392. Abstrak. Anak dan remaja penyandang disabilitas di SLB perlu memiliki pengetahuan tentang strategi coping stres dan memahami tentang kekerasan seksual dan pencegahannya. Pelatihan training of trainers (ToT) bagi para guru di SLB tentang coping stres dan pencegahan serta penanganan kekerasan seksual dilaksanakan dengan tujuan untuk memberikan pengetahuan bagi para siswa di SLB tentang bagaimana mengatasi stres dan mencegah kekerasan seksual yang rentan dialami oleh anak dan remaja penyandang disabilitas. Kegiatan pelatihan ini merupakan suatu bentuk pengabdian kepada masyarakat yang dilakukan pada para guru di SLB Negeri Lobalain, Kabupaten Rote-Ndao. Sebanyak 17 orang guru mengikuti kegiatan pengabdian masyarakat ini. Penelitian kuasi eksperimen dengan one-group pretest-posttest design dilakukan untuk mengukur efektivitas pelatihan. Hasil uji hipotesis menunjukkan bahwa pelatihan yang diberikan berpengaruh signifikan pada pemahaman peserta, t(16) = -5.738, p 0.001, d = -1.392.